Meningkatkan Kemampuan Berbicara Monolog Teks Recount dengan Metode Demonstrasi Media Picture Series - Purna Supriyati (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
The classroom action research (CAC) aimed to solve the 32 SMA Negeri 1 Srandakan Yogyakarta Grade X students’ low competence of recount text monologue. The CAC applied the method of picture series demonstration. The data was collected with observation and testing methods and analyzed with critically comparative and descriptive methods. The research result showed that the students’ activeness is 87.50%. In the first cycle, the students’ test score at average is 75.16 and the mastery of learning is 81.25%. In the second cycle, the students’ test score at average is 80.08 and the mastery of learning is 90.06% that is higher than 80%, the fair score of the mastery of learning. It concluded that the application of the method of picture series demonstration successfully improved the SMA Negeri 1 Srandakan Grade X students’ competence of recount text monologue.